Comparing sound emergence and sound pressure level as predictors of short-term annoyance from wind turbine noise - Dutilleux Guillaume (Acta Acustica, 2020)
While most of the countries over the world rely on sound-pressure-level-based limit values to regulate wind energy development, sound emergence as defined in ISO 1996-1 is used in a few national legislations but also in international guidelines. There is however no published evidence that sound emergence is a relevant noise descriptor for that kind of source, namely that there is a correlation between this metric and perception or annoyance. A listening test was carried out to evaluate the relative merits of sound pressure level and sound emergence as predictors of annoyance from wind turbine noise. The test samples consisted of 45 30-s wind turbine sounds at three different A-weighted sound pressure levels and five different signal-to-noise ratios. Thirty two persons rated the test samples according to the ISO 15666 standard scale in a dry room equipped with loudspeakers. The results indicate that short term annoyance is better predicted by A-weighted sound pressure levels than by sound emergence. It is also observed that sound emergence is a poor predictor of the audibility of wind turbine sounds.